Предмет: Алгебра,
автор: velogamer
Доказать тождество
a*x-y+x-a*y=(x-y)*(a+1)
Ответы
Автор ответа:
0
a*x-y+x-a*y=xa+x-ya-y
a*x-y+x-a*y=ax-y+x-ay
a*x-y+x-a*y=ax-y+x-ay
Автор ответа:
0
просто перемножить надо правую часть
(х-у)*(а+1)= а*х+х-а*у-у= ах-у+х-ау правая часть = левой
(х-у)*(а+1)= а*х+х-а*у-у= ах-у+х-ау правая часть = левой
Похожие вопросы
Предмет: Другие предметы,
автор: sofiya0076
Предмет: Литература,
автор: Bababoi228
Предмет: География,
автор: madirasulov09
Предмет: Геометрия,
автор: Дадашка
Предмет: Алгебра,
автор: Крисстина